Dividing the domestic : men, women, and household work in cross-national perspective - Treas, Judith; Drobnič, Sonja (Studies in social inequality., 2010)
Leading international scholars investigate how culture and country characteristics permeate our households and our private lives. The book introduces novel frameworks for understanding why the household remains a bastion of traditional gender relations - even when employed full-time, women everywhere still do most of the work around the house, and poor women spend more time on housework than affluent women.